2006
DOI: 10.1094/ats-2006-0210-01-tt
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Irrigation Water for Golf Courses in Southeastern Pennsylvania

Abstract: Irrigation water quality is one of the most important environmental issues facing the green industry today, especially in urban areas with competing interests for limited water resources. Fifty‐eight irrigation water survey kits were sent to golf courses within the Groundwater Protected Area of southeastern Pennsylvania. A total of 35 (60%) water samples were received and grouped into one of five water source categories: domestic, lake, recycled, stream, and well. Laboratory analysis measured or calculated 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 4 publications
2
17
3
Order By: Relevance
“…Water quality was best in the Northeast and Transition regions (Table 11). A survey of irrigation water quality of 35 golf courses in southeastern Pennsylvania by Fidanza et al (4) showed a mean TDS of 226 ppm, a mean SAR of 0.7, a mean pH of 6.9, and a mean RSC of 0.02, which were similar to the values from this survey for the Northeast agronomic region.…”
Section: Water‐quality Characteristicssupporting
confidence: 79%
“…Water quality was best in the Northeast and Transition regions (Table 11). A survey of irrigation water quality of 35 golf courses in southeastern Pennsylvania by Fidanza et al (4) showed a mean TDS of 226 ppm, a mean SAR of 0.7, a mean pH of 6.9, and a mean RSC of 0.02, which were similar to the values from this survey for the Northeast agronomic region.…”
Section: Water‐quality Characteristicssupporting
confidence: 79%
“…Carbonate‐cemented layers have never been documented in turfgrass systems, yet there is a widely held belief in the turfgrass industry that bicarbonate from irrigation water can accumulate to cause physical problems in the soil (Carrow et al, 1999; Ellis, 2009; Fidanza et al, 2006; Harivandi, 1999; Simmons, 2010). This has been referred to as a salt‐induced sealing of pores, which is regarded as being distinctly separate from sodium hazard (Carrow and Duncan, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorus was below the laboratory reporting limit (0.03 mg L –1 ) in 50% of the samples in this survey. None of the irrigation water samples in the southeastern Pennsylvania survey had detectable phosphorus concentrations (Fidanza et al., 2006). The normal range for detectable phosphorus concentrations suggested by Ayers and Wescot (1994) and currently listed in PSAASL test reports is 0.1 to 0.4 mg L –1 , which is close to the 10th and 90th percentiles of <0.03 and 0.23 mg P L –1 , respectively, found in this survey.…”
Section: Summary Of Irrigation Water Survey Datamentioning
confidence: 99%
“…Surveys of irrigation water are an important means of assessing the biological and chemical components of water sources, as well as attitudes about water quality among users (Cisar et al., 2006; Fidanza et al., 2006; Meador et al., 2012). Fidanza et al.…”
Section: Introductionmentioning
confidence: 99%